2014
DOI: 10.1016/j.bbagen.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Can we optimise the exercise training prescription to maximise improvements in mitochondria function and content?

Abstract: Abstract:Background: While there is agreement that exercise is a powerful stimulus to increase both

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
143
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(161 citation statements)
references
References 99 publications
11
143
0
7
Order By: Relevance
“…44 No significant changes that could explain the restoration of the respiratory capacity were found in the level of citrate synthase in the proteomics analysis (S1 Table S9). …”
Section: Mitochondria Isolated From Whole Hippocampus Show Dose-depenmentioning
confidence: 92%
“…44 No significant changes that could explain the restoration of the respiratory capacity were found in the level of citrate synthase in the proteomics analysis (S1 Table S9). …”
Section: Mitochondria Isolated From Whole Hippocampus Show Dose-depenmentioning
confidence: 92%
“…In addition, it has been shown that the training response of slow and fast twitch fiber dominated skeletal muscle is very different (Bishop et al, 2014). High intensity training does not cause greater increase in mitochondrial content in slow type of skeletal muscle than low intensity training, while the duration of the training dose is important to increase mitochondrial mass in soleus but not in white vastus lateralis muscle (Bishop et al, 2014). Therefore, despite of the fact that the effects of exercise is systemic (Radak et al, 2008), it is appears that not just muscle type specific but organ specific differences could be present in rats with different aerobic trainability.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences were found in M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), mitochondrial transcription factor A (TFAM), nuclear respiratory factor 1 (NRF-1) and Lon protease in low and high responder group in gastrocnemius muscle. In addition, it has been shown that the training response of slow and fast twitch fiber dominated skeletal muscle is very different (Bishop et al, 2014). High intensity training does not cause greater increase in mitochondrial content in slow type of skeletal muscle than low intensity training, while the duration of the training dose is important to increase mitochondrial mass in soleus but not in white vastus lateralis muscle (Bishop et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Em função disso, a mesma foi considerada a variável mais importante na predição do desempenho de atletas altamente treinados em atividades de longa duração 2 . Mitocôndrias respondem de forma quantitativa e qualitativa ao treinamento físico-esportivo (TFE) com exercícios físicos de longa duração 3 . No primeiro caso, ocorre aumento no volume mitocondrial do tecido, enquanto no segundo, somente na atividade de enzimas e processos de transporte e cinética de reações químicas.…”
Section: Introductionunclassified
“…Por outro lado, o destreinamento e o envelhecimento promovem queda na quantidade e funcionalidade mitocondrial. Portanto, nestes casos, o volume e a duração devem ser enfatizados no treinamento 3 . Em termos funcionais, quando a demanda bioenergética durante o exercício físico é mantida abaixo da "máxima potência oxidativa celular", considera-se que um teto metabólico ("metabolic ceiling") mitocondrial foi estabelecido, sendo possível manter o esforço físico por longo tempo nesse valor de taxa metabólica 6 .…”
Section: Introductionunclassified